Assessment of Aspiration Risk Using the Mann Assessment of Swallowing Ability in Brain-Injured Patients With Cognitive Impairment - Kwon, Shinyoung; Sim, Jaehoon; Park, Joonhyun; Jung, Youngsoo; Cho, Kye Hee; Min, Kyunghoon; Kim, MinYoung; Kim, Jong Moon; Im, Sang Hee (Frontiers in Neurology, 2019)
Objectives The purposes of this study are to determine whether there is a correlation between the Mann Assessment of Swallowing Ability (MASA) and modified MASA (mMASA) according to various cognitive status and to investigate whether the cognitive status of patients with brain damage affects the prediction of aspiration using the MASA. Methods We retrospectively assessed 146 dysphagic patients with brain lesion due to various causes. Dysphagia was assessed using the MASA and mMASA. According to the videofluoroscopic swallowing study results, patients were divided into two groups: aspirators and nonaspirators. Patients were classified into 4 groups according to cognitive function according to the Korean version of Mini-mental State Examination scores: normal (˃24), mild (21-24), moderate (10-20), and severe (<10) cognitive impairment. The correlation between the MASA and mMASA scores according to cognitive function were analyzed. The sensitivity, specificity, and positive and negative predictive values of the MASA scores for predicting aspiration were assessed. Results The MASA and mMASA scores showed a significant positive correlation in all cognition groups. In patients with more severer cognitive impairment MASA scores had high sensitivity and low specificity for prediction of aspiration. On the other hand, the MASA scores had low sensitivity and high specificity for prediction of aspiration in the normal and mild cognitive impairment groups. Conclusions The MASA and mMASA scores correlated with each other in patients with various levels of cognitive function. Interestingly, this study results demonstrated that patients with good cognitive function may have false negative results of MASA screening due to low sensitivity. Thus, when interpreting the MASA results, the impact of cognitive status should be taken into consideration.